Congenital macroglossia: case report of a rare disease - Srivastava, Sandesh; Kumar, Rahul; Sachdeva, Money; Raj, Richa; Singh, Om P. (International Journal of Contemporary Pediatrics, 2022)
Macroglossia is a clinical disorder in which the tongue is larger than normal. Enlargement can be true as seen in vascular malformations or it could be due to muscular enlargement The prevalence of congenital macroglossia is less than 5 per 100,000 birth. Various causes include acromegaly, Beckwith-Wiedemann syndrome, congenital hypothyroidism, Down syndrome, and lymphangioma or haemangioma. It may cause significant symptoms in children such as sleep apnea, respiratory distress, drooling of saliva, difficulty in swallowing and dysarthria. Long-standing macroglossia leads to an anterior open bite deformity, increased incidence of upper respiratory tract infections and failure to thrive.